2020
DOI: 10.2174/1871527319666200117105133
|View full text |Cite
|
Sign up to set email alerts
|

Stingless Bee Honey Reduces Anxiety and Improves Memory of the Metabolic Disease-induced Rats

Abstract: Background: Scientific studies support the evidence of the involvement of Metabolic Syndrome (MetS) in the progression of neurodegenerative diseases through oxidative stress. Consumption of antioxidant compounds was found to be beneficial for brain-health as it reduced the brain oxidative stress level and improved cognitive performance in animals. Stingless bee honey or locally known as Kelulut Honey (KH) has high phenolic content and is widely used as a food supplement. Objectives: In this study, we aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
5
13
0
1
Order By: Relevance
“…Morris water maze test is one of the most widely used tests as hippocampaldependent spatial learning and memory performance (Liu et al, 2014;Wu et al, 2017). In the present study, we found that impairment in both learning and memory performance induced by CUMS was significantly reversed by honey supplementation, which was consistent with previous studies (Abdulmajeed et al, 2016;Arshad et al, 2020;Azman et al, 2015;Azman et al, 2016;Othman et al, 2011). Generally, the evidence indicated that honey supplementation attenuated depression and learning and memory comorbidities induced by CUMS.…”
Section: Discussionsupporting
confidence: 92%
“…Morris water maze test is one of the most widely used tests as hippocampaldependent spatial learning and memory performance (Liu et al, 2014;Wu et al, 2017). In the present study, we found that impairment in both learning and memory performance induced by CUMS was significantly reversed by honey supplementation, which was consistent with previous studies (Abdulmajeed et al, 2016;Arshad et al, 2020;Azman et al, 2015;Azman et al, 2016;Othman et al, 2011). Generally, the evidence indicated that honey supplementation attenuated depression and learning and memory comorbidities induced by CUMS.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, SBH displayed capabilities in improving spatial working memory, spatial reference memory and memory consolidations. Another study also suggested that SBH improves memory and reduces anxiety, in addition to its potential to reduce triglyceride, LDL, and normalize blood glucose in rats with metabolic syndrome [ 24 ].…”
Section: Stingless Bee Honeymentioning
confidence: 99%
“…Meanwhile, SARS-CoV-2 invasion activates multiple signaling cascades that alter metabolism in order to create conditions favorable for viral replication [28,31,62]. Both honey and fermented milk are capable of correcting metabolic dysfunctions [33,144]. Reduction of Firmicutes/Bacteroidetes ratio by probiotics (such as those found in honey and fermented milk) is associated with improvement in metabolism and reduction in toxic metabolites such as chenodeoxycholic acid, deoxycholic acid, lithocholic acid, d-talose, and N-acetylglucosamine, along with decreased depletion of d-glucose and l-methionine, as well as upregulation of the metabolism of pyruvate, retinol, and PPAR in the liver [145].…”
Section: Fermented Milk Supplemented With Honey As a Source Of Bioactive Peptides And Proteinsmentioning
confidence: 99%
“…Neuroprotective Properties of Fermented Milk Supplemented with Honey Experimentally, natural honey is reported to protect astrocytes against oxidative stress, which may be associated with neuroprotection against neurodegeneration [99]. Cumulative knowledge shows that bee honey exerts antidepressant, anxiolytic, and cognitiveenhancing properties in experimental animals and humans [138,144,146,147]. Fermented milk is reported to improve cognitive functioning in experimental animals with induced cognitive dysfunction [148], Alzheimer's disease transgenic mice [149], and healthy older adults undergoing cognitive fatigue [141].…”
Section: Fermented Milk Supplemented With Honey As a Source Of Bioactive Peptides And Proteinsmentioning
confidence: 99%